Hubungan Suhu dan Kelembapan Ruangan Terhadap Sick Building Syndrome (SBS) di UPTD Balai Pengujian dan Sertifikasi Mutu Barang (BPSMB) Samarinda - Lagihara, Chrismasisca Hanni Drescher; Wardani, Pratiwi Sri; Natalisanto, Adrianus Inu (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2024)
Samarinda is one of the cities in East Kalimantan, in Samarinda itself there are many office buildings that use AC coolers. One of the office buildings in Samarinda is the Quality Testing and Certification Center of East Kalimantan’s Building (UPTD. Balai Pengujian dan Sertifikasi Mutu Barang Provinsi Kalimantan Timur). Room temperature and humidity greatly affect the level of worker productivity, but not many people understand the existence of sick building syndrome (SBS). The purpose of this study was to determine the characteristics of employees regarding SBS complaints based on age and length of work and to find out the description of room temperature and humidity at UPTD BPSMB. The type of research used is non-probability sampling with a descriptive approach. The sample in this study were UPTD BPSMB Samarinda employees with a sample size of 20 people. The sampling technique was determined by purposive sampling method. The results of this study showed that the most commonly experienced symptoms were dry skin (50%), drowsiness (40%), dry lips and fatigue (20%), eye irritation, headaches, and difficulty concentrating (15%). From the results of the cross-tabulations that were carried out, it was found that there was no relationship between temperature and SBS, age and SBS, and duration of work with SBS, Still, there was a relationship between humidity and SBS. It is suggested to the UPTD BPSMB to monitor the room at least once a month to see the temperature and humidity conditions of the room so that employees can work comfortably and can increase employee productivity.